2018
DOI: 10.1021/acs.inorgchem.8b00208
|View full text |Cite
|
Sign up to set email alerts
|

Crystal and Magnetic Structures of the Chain Antiferromagnet CaFe4Al8

Abstract: The crystal structure of CaFeAl was studied by X-ray single crystal and powder diffraction as well as high-resolution neutron powder diffraction. CaFeAl crystallizes with a tetragonal CeMnAl-type structure, an ordered variant of the ThMn-type (Pearson symbol tI26, space group I4/ mmm, a = 8.777(1), c = 5.077(1) Å). Similarly to the well-known A15-type superconductors, the structure of CaFeAl contains one-dimensional chains of d-metal atoms, which are parallel to the crystallographic fourfold axis. CaFeAl is pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Earlier Although it is confirmed that there are two magnetic Fe sublattices in the YbFe 4 Al 8 , the exact type of antiferromagnetic configuration is not known. The powder neutron diffraction at 4 K for the isostructural compound CaFe 4 Al 8 has shown that the magnetic moments on the Fe atoms form antiparallel chains oriented along the cdirection and slightly canted from the axis [69], which can be described as a canted AFM-C configuration. Since the FPLO code only allows the calculation of collinear magnetic configurations, we consider for the YbFe 4 Al 8 simplified collinear AFM-C model.…”
Section: Core Level Spectra Yb 4d Fe 2p and Al 2pmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier Although it is confirmed that there are two magnetic Fe sublattices in the YbFe 4 Al 8 , the exact type of antiferromagnetic configuration is not known. The powder neutron diffraction at 4 K for the isostructural compound CaFe 4 Al 8 has shown that the magnetic moments on the Fe atoms form antiparallel chains oriented along the cdirection and slightly canted from the axis [69], which can be described as a canted AFM-C configuration. Since the FPLO code only allows the calculation of collinear magnetic configurations, we consider for the YbFe 4 Al 8 simplified collinear AFM-C model.…”
Section: Core Level Spectra Yb 4d Fe 2p and Al 2pmentioning
confidence: 99%
“…As the initial lattice parameters, we take the values 8.714 and 5.026 Å measured for YbFe 4 Al 8 [2]. Since the literature does not provide atomic positions for the studied compound, we take ini-tial positions from the isostructural CaFe 4 Al 8 (neutron powder data, T = 4 K) [69]. As a result of optimizing the lattice parameters and atomic positions, we obtain the AFM-C structure presented in Table I.…”
Section: Core Level Spectra Yb 4d Fe 2p and Al 2pmentioning
confidence: 99%